Effects of acrylamide and crocin on rat lung tissue (Annals of Medical Research, 2022)
Aim: We aimed to determine the effects of acrylamide (AA) and crocin (Cr) on rat lung tissues.Materials and Methods: Forty Wistar albino rats were divided into control, AA, Cr, and AA + Cr groups. Rats were administered 25 mg/kg AA and 50 mg/kg Cr for 21 days. After 21 days, malondialdehyde (MDA), reduced glutathione (GSH), total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), superoxide dismutase (SOD), catalase (CAT) and protein levels were measured in rat lung tissues.Results: The analysis of the rat lung tissues revealed that oxidant parameter markers (MDA, TOS, OSI) increased and antioxidant parameter markers (GSH, TAS, SOD, CAT) decreased in the AA group when compared to all other groups (p